Quantifying Manual Safeguard Failure Probability in High-Flow Gasoline Tank Overfill: An Integrated SLIM–SHIPP–ETA–LOPA Framework for SIL Specification - Rafi Adisasmito Syamsudin; Ahmad Dani; Indrawan Christano; Adhitya Ryan Ramadhani (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2026)
High-flow gasoline tank filling can escalate to overfill, fire, or explosion when level control relies on manual safeguards. This study quantified manual safeguard failure in a gasoline storage facility operating at 300 kL/h and specified the required automation level. HAZOP identified the critical deviation, ALOHA characterized consequence zones, SLIM estimated operator error probabilities, SHIPP and ETA represented sequential barrier failure, and LOPA determined the required risk reduction. The “More Level” deviation obtained the highest HAZOP priority. Under the adopted modeling assumptions and an assumed initiating event frequency of 1.0 demand per year, ETA estimated failure probabilities of 3.10 × 10⁻¹ for the Ignition Prevention Barrier and 8.54 × 10⁻¹ for the Escalation Prevention Barrier, producing a major fire/explosion scenario frequency of 1.88 × 10⁻³ per year. This value exceeded the adopted target risk of 1.0 × 10⁻⁴ per year and required an RRF of 18.8. The results support implementing a SIL 1 Safety Instrumented System to supplement manual safeguards.